Konsep Pemimpin dalam Islam: Analisis Terhadap Pemikiran Abuya Hamka - Susanti, Fitrina; Fitri, Lidya; Wastri, Linda; Demina (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Buya Hamka's leadership philosophy reflects a holistic approach encompassing spiritual, moral, and social aspects in Islamic leadership. The literature method is employed to analyze key concepts in Buya Hamka's thinking, such as piety, justice, ethics, service, and communication skills, forming the foundation of leadership. The analysis results indicate that Buya Hamka places piety as the primary foundation, emphasizing obedience to Allah as the moral and spiritual basis for a leader. Justice is considered an uncompromisable principle guiding decision-making. Good ethics serves as the moral foundation, while serving the community is the primary goal of a leader. Effective communication skills are also emphasized as a tool to build strong relationships between leaders and their constituents. This philosophy remains relevant in the contemporary context, providing guidance on Islamic values for leaders and the general community, fostering a better social environment.